Ascites and Serial Plasma Circulating Tumor DNA for Predicting the Effectiveness of Hyperthermic Intraperitoneal Chemotherapy in Patients With Peritoneal Carcinomatosis - Pu, Xiaolin; Li, Zongyuan; Wang, Xiaoying; Jiang, Hua (Frontiers in Oncology, 2022)
Purpose: We investigated the value of ascites and serial plasma circulating tumor DNA (ctDNA) for predicting response to hyperthermic intraperitoneal chemotherapy (HIPEC), monitoring tumor burden, and predicting prognosis in patients with peritoneal carcinomatosis (PC). Experimental Design: In this observational study, 19 patients with PC were enrolled. Serial plasma ctDNA was analyzed using next-generation sequencing. The molecular tumor burden index (mTBI) was used to detect ctDNA, and concurrent changes in the dominant clone variant allele frequency (VAF) and common tumor markers were used as controls. The correlation between ascites and plasma ctDNA comutated genes was expressed by VAF. The overall response rate (complete response + partial response) after HIPEC was determined. Ascites progression-free survival (PFS) and overall survival (OS) were determined, and potential correlations between these outcomes and change in mTBI (△mTBI), change in sum-VAF (△sum-VAF), dominant close VAF, and tumor markers were assessed. Results: The overall response rate at 1 month after HIPEC was 100%. The △mTBI (r = 0.673; P = 0.023) and △sum-VAF (r = 0.945; P <0.001) were significantly positively correlated with ascites PFS; these correlations were stronger than those of the dominant clone VAF (r = 0.588; P = 0.057) and tumor markers in the same period (r =0.091; P = 0.790). Patients with a low baseline mTBI (<0.67) demonstrated significantly longer ascites PFS (P = 0.003; HR = 0.157; 95% CI: 0.046–0.540) and OS (P = 0.017; HR = 0.296; 95% CI: 0.109–0.804) than those with a high baseline mTBI (≥0.67). Consistent mutations were detected in plasma and ascites (r = 0.794; P = 0.001). Conclusion: A real-time serial plasma ctDNA assay accurately reflected tumor burden. The △mTBI and △sum-VAF can be used as predictors of HIPEC efficacy in patients with PC. A high baseline mTBI may be a negative risk factor for prognosis.